KAJIAN ETNOMATEMATIKA PADA BENTUK DAN UKURAN BATU LOMPAT DALAM TRADISI HOMBO BATU DIPULAU NIAS - Hulu, Yukalfin; Jesse Erikson Hutagaol; Sindi Nababan; Santa Sinaga; Friska ledina Situngkir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Culture is the realization of norms, values, and customs that takes important role in education field particularly in the learning of mathematics. South Nias with rich cultures can become reference for mathematics teacher to create media of learning. The very interesting culture that can be used as the media of learning of mathematics is culture which named “hombo batu”. This research aims at identifying hombo batu and describing the mathematics concept that found within it so it can be used as the media of learning of mathematics. This research is designed in qualitative research design through ethnography research approach. The focus of this research is culture “hombo batu” in South Nias Regency. The techniques of data collection that used are observation, intervew and documentation. Based on the results of research and discussion, hombo batu has four mathematical concepts in general, they are truncated rectangular pyramid off at each corner points, edges, side or field, diagonal side, diagonal space, rectangle, trapezoid, nets surface area and volume; the similarities are congruent and congruent respectively, the transformation geometry of each reflection and dilatation, and number patterns, so that the hombo batu culture can be used as a medium for learning mathematics.